Esencia y modalidad: Husserl y Kripke - Romano, Claude (ARFIL y UNL, 2018)
This paper analyzes Husserl’s and Kripke’s notions of essence in order to show relations and differences between them. Husserl excludes a modal definition of essence, considering that unconditional necessities have their origin in essences, but not reciprocally. Kripke’s conception, on the other hand, obliges us to think again notions that were evident to Husserl, as the “a priori/necessary” and “a posteriori/contingent” equivalences, and also the links between conceivability and possibility. Finally, taking distance from Husserl’s position and his eidetic variation, we emphazise reasoned discussion as the best method in this respect.